Sterol Metabolism and Transport in Atherosclerosis and Cancer - Yamauchi, Yoshio; Rogers, Maximillian A. (Frontiers in Endocrinology, 2018)
Cholesterol is a vital lipid molecule for mammalian cells, regulating the fluidity of biological membranes, and serving as an essential constituent of lipid rafts. Mammalian cells acquire cholesterol from extracellular lipoproteins and from de novo synthesis. En route to cholesterol biosynthesis, various precursor sterols are generated. Cholesterol undergoes metabolic conversion into oxygenated sterols (oxysterols), bile acids, and steroid hormones. Cholesterol intermediates and metabolites have diverse and important cellular functions. Sterol homeostasis in mammalian cells and in tissues is regulated by a network of molecular machineries including transcriptional factors, protein modifiers, sterol transporters/carriers, and sterol sensors. Dysfunction in metabolism and transport of cholesterol, sterol intermediates, and oxysterols occurs in various pathophysiological settings such as atherosclerosis, cancers, and neurodegenerative disease. Here we review the cholesterol, intermediate sterol, and oxysterol regulatory mechanisms and intracellular transport machineries, and discuss the roles of sterols and sterol metabolism in human diseases.